Aortic and Systemic Arterial Stiffness Responses to Acute Exercise in Patients With Small Abdominal Aortic Aneurysms. (November 2019) - Perissiou, Maria; Bailey, Tom G.; Windsor, Mark; Greaves, Kim; Nam, Michael C.Y.; Russell, Fraser D.; O'Donnell, Jill; Magee, Rebecca; Jha, Pankaj; Schulze, Karl; Leicht, Anthony S.; Golledge, Jonathan; et al.
Abstract : Objective/background: Elevated arterial stiffness is a characteristic of abdominal aortic aneurysm (AAA), and is associated with AAA growth and cardiovascular mortality. A bout of exercise transiently reduces aortic and systemic arterial stiffness in healthy adults. Whether the same response occurs in patients with AAA is unknown. The effect of moderate- and higher intensity exercise on arterial stiffness was assessed in patients with AAA and healthy adults. Methods: Twenty-two men with small diameter AAAs (36 ± 5 mm; mean age 74 ± 6 years) and 22 healthy adults (mean age 72 ± 5 years) were included. Aortic stiffness was measured using carotid to femoral pulse wave velocity (PWV), and systemic arterial stiffness was estimated from the wave reflection magnitude (RM) and augmentation index (Alx75). Measurements were performed at rest and during 90 min of recovery following three separate test sessions in a randomised order: (i) moderate intensity continuous exercise; (ii) higher intensity interval exercise; or (iii) seated rest. Results: At rest, PWV was higher in patients with AAA than in healthy adults ( p  < .001), while AIx75 and RM were similar between groups. No differences were observed between AAA patients and healthy adults in post-exercise aortic and systemic arterial stiffness after either exercise protocol. When assessed as the change from baseline (delta, Δ), post-exercise ΔAIx75 was not different to the seated rest protocol. Conversely, post-exercise ΔPWV and ΔRM were both lower at all time points than seated rest ( p  < .001). ΔPWV was lower immediately after higher intensity than after moderate intensity exercise ( p  = .015). Conclusion: High resting aortic stiffness in patients with AAA is not exacerbated after exercise. There was a similar post-exercise attenuation in arterial stiffness between patients with AAA and healthy adults compared with seated rest. This effect was most pronounced following higher intensity interval exercise, suggesting that this form of exercise may be a safe and effective adjunctive therapy for patients with small AAAs.